Novos compostos de íons lantanídeos com ligantes β- dicetonatos: síntese, caracterização e propriedades luminescentes - ROSA, Jéssica Maria Luis (2017)
A mechanism of intramolecular energy transfer via absorption of the radiation in the ultraviolet region by the ligand, non-radiatively for the Ln3+ ion, was established, and then the emission of radiation in the region of the visible. This process is antenna effect. Therefore, this work aimed to provide a better understanding of the structures of the complexes and interactions between the antenna ligands and the Ln3+ metal center. The complexes [Ln(acac)(NO3)2(phen)2] (Ln = Eu3+ and Tb3+) were synthesized and characterized by infrared spectroscopy, confirming the presence of the ligands used in the synthesis of the compound. The photoluminescent study carried out from its excitation and emission spectra shows that the thin bands characteristic of the interconfiguration transitions of the lanthanide ions are presented, with the colors red for Europium and green for the Terbium. The emission spectra did not show the broadband related to the acac binder, indicating that the processes of energy transfer from the triplet state of the binder to the excited levels of the lanthanide ion are efficient. The quantum efficiency value of the complex containing Eu3+ was of 64.25%, a very satisfactory result.